2016
DOI: 10.1186/s13104-016-2173-5
|View full text |Cite
|
Sign up to set email alerts
|

Intensive social cognitive treatment (can do treatment) with participation of support partners in persons with relapsing remitting multiple sclerosis: observation of improved self-efficacy, quality of life, anxiety and depression 1 year later

Abstract: BackgroundIn persons with multiple sclerosis (MS) self-efficacy positively affects health-related quality of life (HRQoL) and physical activity. In a previous study we observed that 6 months after an intensive 3-day social cognitive treatment (Can Do treatment) with the participation of support partners, self-efficacy and HRQoL had improved in persons with relapsing remitting MS (RRMS). Given the chronic nature of the disease, it is important to know whether these beneficial changes may last.MethodsCan Do trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…After the baseline assessment (T0), follow-up assessments took place at 1 month (T1), 3 months (T2), and 6 months (T3). The 6-month follow up of the study was chosen as the observational study previously performed in MS patients with the same intervention in the Netherlands showed an effect after 6 months 15 . In addition, in a chronic disorder like MS, an effect shorter than 6 months would have limited clinical relevance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the baseline assessment (T0), follow-up assessments took place at 1 month (T1), 3 months (T2), and 6 months (T3). The 6-month follow up of the study was chosen as the observational study previously performed in MS patients with the same intervention in the Netherlands showed an effect after 6 months 15 . In addition, in a chronic disorder like MS, an effect shorter than 6 months would have limited clinical relevance.…”
Section: Methodsmentioning
confidence: 99%
“…4. CDT is a standardized intervention, which has been described in detail in order to make replication of the treatment and further research possible 15,16,19 . 5.…”
Section: Practical Implications Of the Study Findings And Current Knomentioning
confidence: 99%
See 2 more Smart Citations
“… 6 In a subsequent study, it was found that 12 months after treatment, RRMS patients had an increased physical HRQoL (+15.0%) and decreased depression (−29.8%) and anxiety (−25.9%). 10 …”
Section: Introductionmentioning
confidence: 99%